2018
DOI: 10.1007/s10894-018-0185-y
|View full text |Cite|
|
Sign up to set email alerts
|

DIII-D Research to Prepare for Steady State Advanced Tokamak Power Plants

Abstract: We review progress made on the advanced tokamak path to fusion energy by the DIII-D National Fusion Facility (Luxon et al. in Nucl Fusion 42:614, 2002). The advanced tokamak represents a highly attractive approach for a future steady state fusion power plant. In this concept, there is a natural alignment between high pressure operation, favorable stability and transport properties, and a highly self-driven ('bootstrap') plasma current to sustain operation efficiently and without disruptions. Research on DIII-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 146 publications
(205 reference statements)
1
34
0
Order By: Relevance
“…In other words, this turbulence outside an MI can spread into the MI if its amplitude is sufficiently large 30 . In the recent DIII-D 31 and HL-2A 32 experiments 12 , 33 , 34 , observations which seem to result from the spreading of the density and temperature turbulence towards the O-point of an MI are reported. In addition, the nonlinear electrostatic gyrokinetic simulation based on the KSTAR plasma equilibrium and profiles showed that turbulence and the heat can spread into an MI which was initially stable region 35 .…”
Section: Resultsmentioning
confidence: 96%
“…In other words, this turbulence outside an MI can spread into the MI if its amplitude is sufficiently large 30 . In the recent DIII-D 31 and HL-2A 32 experiments 12 , 33 , 34 , observations which seem to result from the spreading of the density and temperature turbulence towards the O-point of an MI are reported. In addition, the nonlinear electrostatic gyrokinetic simulation based on the KSTAR plasma equilibrium and profiles showed that turbulence and the heat can spread into an MI which was initially stable region 35 .…”
Section: Resultsmentioning
confidence: 96%
“…10 seems unexpected. For the force and the so-called sideways (lateral) force, the following equality is valid [53]: (16) where c is the constant vector ( to obtain the ), and the integration is performed over an axially symmetric toroidal shell that encloses the wall from the outside. At the initial time, when there are no currents in the wall, the force acting on the wall is zero, .…”
Section: Discussionmentioning
confidence: 99%
“…Here, the plasma and wall are vertically elongated, but it can be expected that the main dependencies found in [23][24][25][26] should also manifest themselves in our case too [22,31,32]. In particular, we will check the prediction that a strong radial force can be generated during the TQ before the CQ start, although the presence of dangerous electromagnetic loads in tokamaks is usually associated with the current quench [6,7,[11][12][13][14][15][16][17][18][19][33][34][35][36][37][38][39][40][41][42][43][44], sometimes explicitly noting that the force is proportional to [7,36,42].…”
Section: Formulation Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations